ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PENDAPATAN DI JAWA TIMUR - Raihan Daffa Naufal; Santoso, Dwi Budi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The welfare of the community is the primary goal in the economic development of a region, and this can be achieved through rapid economic growth and equitable income distribution. In reality, East Java Province has not yet achieved equal prosperity, as evidenced by an increasing trend of inequality that has not reached its lowest point during the period of this research. Therefore, there is a need to accelerate the reduction of inequality by understanding the various factors influencing inequality in East Java. Through a simultaneous model using the three-stage least square (3SLS) method, this study attempts to estimate the impact of Gross Regional Domestic Product (PDRB) per capita and the health index on income inequality. It also analyzes the factors influencing the growth of PDRB per capita in East Java. The data used for this research is sourced from the Badan Pusat Statistik (BPS) for the years 2011-2021.The research findings indicate that the growth of PDRB per capita and the health index significantly and positively affect income inequality. The factors influencing the growth of PDRB per capita in East Java include the education index and capital accumulation. Based on these results, the government and relevant stakeholders need to promote a more even distribution across sectors in each region of East Java Province and strengthen health aspects for groups with low incomes.